Discourse Connectors in Udin Bounyavong’s “From Ten Years Ago volume 3” Short Story - Khanthavongxay, Phoukham; PAPHAPHANH , Bualy (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research aims to analyze cohesive units based on their semantic types and functions in the short story collection “From Ten Years Ago, Volume 3”, a masterpiece of children’s literature by Udin Bunyawong, an outstanding literary artist in the field of literature in 2010. The collection comprises 11 short stories. The statistical method used for data analysis is percentage. The Result found that cohesive unit functions are divided into 2 types: micro-level cohesive units and macro-level cohesive units. For the semantic types of micro-level cohesive units, there are 8 subtypes, ranked by frequency of use from highest to lowest. They are contrastive (18.42%), causal (16.45%), elaboration (15.13%), conditional (12.50%), alternative (11.18%), temporal (9.87%), exemplificatory (8.55%), conclusion(7.89%). For the semantic types of macro-level cohesive units, there are 5 subtypes, ranked by frequency of use from highest to lowest. They are contrastive (23.68%), causal (21.71%), conclusion (19.74%), sequence (18.42%), and elabora- tion (16.45%).